The effects of surface type on the removal of Bacillus cereus and Pseudomonas fluorescens single and dual species biofilms - Madalena Lemos (2015)
The aim of this work was to assess the effectiveness of the biocide benzyldimethyldodecyl ammonium chloride (BDMDAC) on the removal of single and dual species biofilms of Bacillus cereus and Pseudomonas fluorescens formed in a rotating cylinder reactor (RCR), using AISI316 stainless steel (SS) and polymethyl methacrylate (PMMA) as adhesion surfaces. Additional tests were performed to understand the adhesion of B. cereus and P. fluorescens to the selected surfaces. Predictions of the adhesion potential according to the thermodynamic theory showed more favourable adhesion on SS than on PMMA, for both species. Thermodynamically, adhesion was more favourable for B. cereus. After BDMDAC treatment, thermodynamic adhesion ability was favoured for P. flurescens and decreased for B. cereus, mainly on PMMA. Both bacteria had negative surface charge and the exposure to BDMDAC increased the charge to less negative values. In vitro adhesion results were, for most cases, contradictory to those predicted by the thermodynamic theory. Single and dual species biofilms were formed in-the RCR for 7 days. Afterwards, the biofilms were exposed to the chemical (use of BDMDAC) and to hydrodynamic stresses (use of increasing Reynolds number of agitation), alone and combined. The applications of BDMDAC or hydrodynamic stress, when applied alone, were insufficient to remove the biofilms from the surfaces. The combined effects of BDMDAC with a series of increasing Reynolds number of agitation promoted additional biofilm removal. This effect was dependent on the surface used. For PMMA, the hydrodynamic stress was more effective on the removal of BDMDAC-treated dual species biofilms. For SS, the synergy of the chemical and hydrodynamic stresses removed more B. cereus and dual species biofilms. The overall results demonstrate that the species association was not advantageous in biofilm resistance to removal when compared with the single species biofilms, particularly those of P. fluorescens. In general, removal by hydrodynamic stress, alone and preceded by the BDMDAC treatment, was higher for biofilms formed on SS. However, even the combined action of BDMDAC and the exposure to a series of increasing Reynolds number of agitation were not effective to obtain biofilm-free surfaces.